Does prior misconduct predict drug use by police? - Cubitt, Timothy (Policing and society, 2024)
Recent research has yielded important insight into the characteristics and behaviours of officers who commit misconduct across the UK, USA and Australia. However, there remains little research into illicit substance use by sworn police. Considering substance use by police through the lens of police misconduct, this paper employs correlation and regression analyses using a sample of 489 sworn officers, to analyse whether individual types of misconduct, or the overall volume of misconduct committed, were predictive of an officer returning a positive drug test during departmental random drug testing. Findings suggested that neither individual types of misconduct, or the overall number of complaints received by officers were useful in predicting a positive drug test. However, a current or historical association with a known offender held a strong relationship with returning a positive drug test. Pivotally, holding a second job (outside of the agency) was also a significant predictor of a positive drug test. The findings of this research hold important implications for drug testing policy and procedure of policing agencies, and for understanding which factors may suggest that an officer is at risk of drug use.